Study on analysis of gender disparities among the first authors of publications on Menetriers disease - Gomma, Ahmed; Mohamed, Muawia Yousif Fadlelmola; Menon, Vyshnav Rajagopal; Elameen, Hozaifa; Krishnan, Aparna (International Journal of Advances in Medicine, 2024)
The disparities in gender representation within academic writing highlight pervasive social prejudices and inequalities, with male researchers predominating in both quantity and visibility, perpetuating a cycle of unequal representation. This imbalance limits the diversity of perspectives in intellectual discourse. However, there has been a noticeable increase in the representation of female authors, breaking traditional gender barriers. This research article aims to investigate gender disparities among first authors in medical literature concerning Menetrier’s disease over the past 22 years. A cross-sectional study of 130 relevant publications from PubMed between January 2001 and December 2022 was conducted, analyzing the gender distribution of first authors using SPSS software. Results indicate that 70.7% of the articles had male first authors, with intermittent periods of female author prominence. While countries like China, Spain, and Italy showed relatively equitable gender ratios, others such as Japan, Turkey, India, and the Republic of Korea exhibited significant male dominance. However, no significant association between gender and country of authors was found. Despite these findings, limitations include potential errors in gender determination methods, focusing solely on first authorship, and overlooking contributions from co-authors, while the selected journals and countries may not fully represent global gender disparities.